1994
DOI: 10.1007/bf00376767
|View full text |Cite
|
Sign up to set email alerts
|

Urine excretion of androgen hormones in professional racing cyclists

Abstract: This study was performed on 16 professional racing cyclists to examine changes in urine concentrations of androgen hormones (testosterone, epitestosterone, androsterone, etiocholanolone, 11-hydroxy-androsterone and 11-hydroxy-etiocholanolone) and plasma sex hormone binding globulin (SHBG) after training and after competition. The urinary concentrations of androgen hormones decreased during the period of training and increased during competition, this being the reverse of what happened to SHBG plasma concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Comparatively, few experimental studies have measured competition- or exercise-induced testosterone changes in urine, but at least one study of cyclists showed that urinary testosterone is increased as a function of competition (Maynar et al, 1994). Moving forward, athletes and testing authorities would each benefit from rigorous studies that examine variation in the T/E ratio in multiple bodily fluids (e.g., urine, serum, and saliva) as a function of pre- and post-competition changes in testosterone.…”
Section: Exogenous Testosterone and Aasmentioning
confidence: 99%
“…Comparatively, few experimental studies have measured competition- or exercise-induced testosterone changes in urine, but at least one study of cyclists showed that urinary testosterone is increased as a function of competition (Maynar et al, 1994). Moving forward, athletes and testing authorities would each benefit from rigorous studies that examine variation in the T/E ratio in multiple bodily fluids (e.g., urine, serum, and saliva) as a function of pre- and post-competition changes in testosterone.…”
Section: Exogenous Testosterone and Aasmentioning
confidence: 99%
“…The variations in the urinary concentration of androgens are in opposition to the changes in SHBG plasma levels [31]. On the other hand, our study shows that physical activity in itself can decrease the ratio of urinary excretions of testosterone and epitestosterone to about 25% (0.87 vs 0.66).…”
Section: Discussionmentioning
confidence: 79%
“…The ratios T/Et and A/E tended to decrease. In men practicing endurance sports it was proved that androgens concentration decrease during training and increase during competition, however, the value of T/Et ratio remains unchangeable [13,14]. …”
Section: Instrument Gc/msmentioning
confidence: 99%